Silicon-related materials demand and embodied greenhouse gas emissions of photovoltaic systems in China's regions - Xu, Xiaozhu; Chen, Xing; Wang, Heming; Zhao, Lianzheng; Wang, Zhi; Chen, Wei-Qiang (Resources, conservation and recycling, 2025)
China is the world's largest producer and consumer of solar photovoltaics (PV). A regional level study of the demand for silicon-related materials (Silica sand, MG-Si, SoG-Si, Wafers, Cells) and embodied GHG emissions in China's photovoltaic industry could provide a scientific basis for its refined policy design. In this study, the demand for silicon-related materials for PV systems and embodied greenhouse gas emissions in 32 provinces and regions in China were assessed under different scenarios using dynamic material flow analysis. The results indicate that under the NZE scenario, from 2021 to 2050, China's PV systems will require 108 Mt of silicon, with cumulative emissions of 313 Mt CO₂-equivalent (Mono-route: 294 Mt, Mult-route: 19 Mt). These emissions are primarily concentrated in the Shandong, Hebei, and Zhejiang regions. In the future, priority should be given to establishing PV module recycling projects in these areas. [Display omitted]